Pengembangan Arsitektur Knowledge Management System Untuk Model Bisnis Pendidikan Tinggi - Ratwiyanti, Puji; Harisno, Harisno (Puslitbang Sekawan Institute Nusa Tenggara, 2023)
The purpose of this study is to design and develop architecture and application of Knowledge Management System (KMS) with a deep and comprehensive analysis at XYZ University. To get a deep and comprehensive analysis, several tools and methods are needed. The collaboration is contained in the stages of this study, starting from the business area analysis to map the subjects needed in making databases, current condition analysis by mapping the needs of knowledge and measuring KM Readiness with Rao scale. Both analyzes produce centralized KMS architectural recommendations, website -based KM application designs accompanied and cost benefits analysis. The conclusion obtained is the Knowledge Management System is one of the real solutions for the organization in giving contributions to improvement of governance and human resources in the organization, the readiness of the organization in implementing knowledge management also affects the process of developing knowledge management systems, technology is one aspect which contributes to the development of knowledge management, besides that the Knowledge Manage-Ment System can be developed into tools to assist management in assessing employee activity aspects.